PEMANFAATAN LIMBAH AMPAS TEBU (BAGASSE) UNTUK PRODUKSI BIOETANOL MELALUI PROSES SAKARIFIKASI DAN FERMENTASI SERENTAK - Candra Daty Novitasari, Astri Ani, Rigandita Ekawati (Pelita - Jurnal Penelitian Mahasiswa UNY, 2012)
The aim of this research is to describe the process of bio ethanol production frombagasse with simultaneous sacharification and fermentation.The subject of this research was bagasse. The object of research was the amount of bioethanol from fermentation of bagasse using Sacharomyces cerevisiae. The independentvariable in this research was the concentration of yeast in the fermentation. There were0.4%; 0.6%; and 0.8% of solution weight. The chemistry analysis in the research was aquantitative and qualitative analysis of ethanol using Micro Conway Diffusion and spectronic20.The results showed the yeast concentration of 0.4% by weight solution of the hydrolysis,ethanol result was 24.555%. In the yeast concentration of 0.6% by weight of hydrolysissolution, the ethanol content was 39.571%. In the yeast concentration of 0.8% by weight ofhydrolysis solution, 35.005% of ethanol was obtained. It was the highest level of ethanol onyeast concentration of 0.6% by weight solution of the hydrolysis.Keywords: bagasse, bio ethanol, fermentation, yeast, sacharification